Simulation video transmission systems using methods of spatial and temporal interpolation - Мороз, В. В. (Problems of Informatization and Control, 2008)
The model of the transmission system of video sequences in order to reduce the volume of information transmitted. For this time involved mechanisms decimation reduced resolution frames and statistical compression . Restoration of the information on the receiver side is performed by methods of spatial and temporal interpolation . Predlalozhenna model of the system allows you to receive high-quality video playback on the visual side of the receiver with a minimum load of the transmission channel